Transverse Vibration Control of Axially Moving Beams by Regulation of Axial Velocity - Nguyen, Quoc Chi; Hong, Keum-Shik; Ge, Shuzi Sam (IFAC Proceedings Volumes, 2011)
In this paper, a novel control algorithm for suppression of the transverse vibration of an axially moving system is presented. The principle of the proposed control algorithm is the regulation of the axial transport velocity of an axially moving system so as to track a profile according to which the vibration energy decays most quickly. The optimal control problem that generates the proposed profile of the axial transport velocity is solved by the conjugate gradient method. The Galerkin method is applied in order to reduce the partial differential equation describing the dynamics of the axially moving beam into a set of ordinary differential equations (ODEs). For control design purposes, these ODEs are rewritten into state-space equations. The vibration energy of the axially moving beam is represented by the quadratic form of the state variables. In the optimal control problem, the cost function modified from the vibration energy function is subject to the constraints on the state variables, and the axial transport velocity is considered as a control input. Numerical simulations are performed to confirm the effectiveness of the proposed control algorithm.